Oral tolerance of Caloreen in babies. Issue 11 (November 1980) - Russell, G; Costalos, C
Abstract : Serial plasma glucose concentrations were compared in 20 infants of low birthweights (< 2500 g) after test meals of 10% solutions of Caloreen and glucose. After Caloreen, the rise in plasma glucose concentration occurred more slowly but was better sustained, and hyperglycaemia was seen less often than after glucose. Caloreen may be preferable to glucose as a carbohydrate source in the prophylaxis and treatment of neonatal hypoglycaemia.